Un fragmento de manuscrito visigótico con texto de las etimologías - Suárez González, Ana (Estudios humanísticos. Geografía, historia y arte, 1996)
We present the detailed study of a new fragment of manuscript in visigothic writing, dated in the middle of the Xth century, and preservad in the Library of San Isidoro of León. It is a bifolium of parchment which contains text from d’Etymologiarum libri XX.